Deepening Cinematography Material to Improve the Skills of Strada Damos Tangerang Vocational School Students - FX. Damarjati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Visual arts, especially photography and videography, have become the main commodity in providing social media content. Lots of photos and videos are produced by social media users to fulfill their desire to appear and get additional benefits from the results of this content. This phenomenon opens up opportunities for Strada Damos Vocational High School students to prepare their graduates to be more creative and master photography and videography techniques. To support the competence of Strada Damos Vocational High School students, during this semester's community service the authors designed a cinematography training program that was adapted to the SKKNI photography and videography competencies so that it could prepare students for the official professional competency test held by the state. Methods This training is divided into 5 meetings whose contents consist of basic photography and videography, practice of mastering equipment and practice of making short videos according to ideas from students. These steps are carried out so that students can understand the process of video production from pre-production, production and post-production. The author does not limit the medium of equipment used to use a DSLR, Handycamp, or even a smartphone camera. This is done so that students do not have to be fixated on the equipment but rather on the conceptual ideas they will make happen.